2017
DOI: 10.1016/j.foodres.2017.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the combination of ω-3 PUFAs and proanthocyanidins on the gut microbiota of healthy rats

Abstract: ω-3 Polyunsaturated fatty acids (PUFAs) reduce risk factors for cardiovascular diseases (CVD) and other pathologies that involve low-grade inflammation. They have recently been shown to exert complementary functional effects with proanthocyanidins. As the reduction of health-promoting gut bacteria such as lactobacilli and bifidobacteria has been linked to a number of alterations in the host, the aim of this study was to determine whether PUFAs and proanthocyanidins also cooperate in maintaining well-balanced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…Recent studies have demonstrated that common prebiotics, such as Lactobacillus can reduce the levels of the systemic inflammation marker (TNF‐α), [ 70 ] Lactobacillaceae can participate in the microbial anti‐oxidation metabolic pathway, [ 71 ] and Lactobacillales can play an important role in maintaining the levels of the intestinal microbiome and SCFAs. [ 72 ] In this study, the correlation analysis indicated that Bacilli , Lactobacillales , Lactobacillaceae , and Lactobacillus can reduce LPS transportation and liver damage by restoring the intestinal barrier functions. However, Blautia , Rothia , Proteobacteria , and Actinobacteria increased LPS transportation and liver damage by decreasing the intestinal barrier functions.…”
Section: Discussionmentioning
confidence: 77%
“…Recent studies have demonstrated that common prebiotics, such as Lactobacillus can reduce the levels of the systemic inflammation marker (TNF‐α), [ 70 ] Lactobacillaceae can participate in the microbial anti‐oxidation metabolic pathway, [ 71 ] and Lactobacillales can play an important role in maintaining the levels of the intestinal microbiome and SCFAs. [ 72 ] In this study, the correlation analysis indicated that Bacilli , Lactobacillales , Lactobacillaceae , and Lactobacillus can reduce LPS transportation and liver damage by restoring the intestinal barrier functions. However, Blautia , Rothia , Proteobacteria , and Actinobacteria increased LPS transportation and liver damage by decreasing the intestinal barrier functions.…”
Section: Discussionmentioning
confidence: 77%
“…A study by Ramos‐Romero et al. showed that GSE significantly reduces the population of Lactobacillus plantarum species (Firmicutes) and Bifidobacterium longum (Actinobacteria) in healthy rats (Ramos‐Romero et al., ); however, it significantly increases the total population of the genus Lactobacillus to which L. plantarum belongs to (Choy et al., ). Also, GSE was introduced to pig models in three different studies, and different results were obtained.…”
Section: Impacts Of Proanthocyanidins On Gut Microbiotamentioning
confidence: 99%
“…A summary of the most relevant biochemical and biometric parameters of rats fed STD diets is shown in Table 2. These parameters have already been studied in the same cohort of animals and partially published [15,19,23]. The supplementation of STD with FOM, GSE or both showed no changes in weight increase but rendered more adiposity index, especially with GSE supplementation.…”
Section: Effects Of Fish Oil Mixture (Fom) and Grape Seed Polyphenolsmentioning
confidence: 96%
“…These parameters have already been studied in the same cohort of animals and partially published [15,22,23]. Rats fed the HFHS control diet developed a prediabetic state characterized by hyperinsulinemia and excess of visceral fat [13,19]. Results indicated that none of the supplementations influenced weight increase as well as adiposity and hepatosomatic indexes.…”
Section: Effects Of Fish Oil Mixture (Fom) and Grape Seed Polyphenolsmentioning
confidence: 99%